Chemical Modification of Kola-Nut (Cola Nitida) Testa for Adsorption of Cu2+, Fe2+, Mg2+, Pb2, and Zn2+ from Aqueous Solution - Slyvanus, Nwafor Ogechi; John, Chukwu Uche; Jnr, Horsfall Mike (Makara Journal of Science, 2020)
In this study, kola-nut testa samples were modified with 0.1 M acetic acid and 0.1 M EDTA at room temperature. The modified Kola-nut testa samples were then characterized with respect to their pH at point of zero charge, melting point, specific gravity, Fourier-transform infrared (FTIR) spectra, and solubility. The characterization results of the modified Kola-nut testa (MKT) revealed that it was sparingly soluble in water, ethanol, and acetone but insoluble in n-hexane. The MKT had a specific gravity of 0.992 ± 0.020 and exhibited various pH values of 4.50 ± 0.50 and 12.00 ± 0.50 at the point of zero charges. The FTIR spectra of the MKT indicated the presence of –OH and –NH groups at 3310.97 cm−1, alkyl groups at 2928.53 cm−1, and aromatic rings at 1612.27–1529.81 cm−1. The results of the adsorption studies at various time intervals indicated that MKT had the capacity to adsorb Fe2+, Mg2+, Zn2+, Cu2+, and Pb2+ as follows: 1.90 ± 0.30 mg/g, 1.80 ± 0.20 mg/g, 1.40 ± 0.20 mg/g, 0.10 ± 0.01 mg/g, and 0.05 ± 0.01 mg/g, respectively. Thus, Fe2+, Mg2+, and Zn2+ were quantitatively removed from the aqueous solutions, whereas Cu2+ and Pb2+ were not. The adsorption of Fe2+, Mg2+, Zn2+, Cu2+, and Pb2+ by MKT from the aqueous medium was dependent on certain factors such as pH, temperature, adsorbent dosage, contact time, and initial metal-ion concentration.